Pengaruh Debt To Equity Ratio dan Return On Asset Terhadap Price Book Value Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Radiman Radiman; Tsamara Athifah (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine and analyze the effect of Debt To Equity Ratio and Return On Assets on Price to Book Value with Managerial Ownership as Moderation Variables in Property and Real Estate Companies Listed on the Indonesia Stock Exchange. This research uses an associative approach method. The population used in this study were 61 property and real estate companies listed on the Indonesia Stock Exchange. While the sample taken is 12 companies using purposive sampling. TThe data analysis technique in this study is to use regression multiple linear. The results of this study indicate partially that the Debt To Equity Ratio has no significant effect on the Price Book Value. Return On Asset has a significant effect on Price Book Value. Debt To Equity Ratio does not moderate the effect insignificantly on Managerial Ownership. Return On Asset does not moderate the effect insignificantly on Managerial Ownership. Simultaneously there is a significant influence between Debt To Equity Ratio and Return On Asset Against Price Book Value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange